Reconstruction Using Frozen Autograft for Disseminated Phosphaturic Mesenchymal Tumor of the Humerus after a Pathological Fracture - Hiroshi Kobayashi; Toshihide Hirai; Naohiro Makise; Tetsuo Ushiku; Nobuaki Ito; Minae Koga; Masachika Ikegami; Yusuke Shinoda; Toru Akiyama; Sakae Tanaka (Case Reports in Orthopedics)
Phosphaturic mesenchymal tumors (PMTs) that cause tumor-induced osteomalacia (TIO) occur commonly in the bone with a small and nonaggressive appearance. Here, we report the case of a 67-year-old man with disseminated PMT in the humerus after a pathological fracture. Liquid nitrogen was used as an adjuvant therapy after curettage of the tumor, and the frozen autograft, using a pedicle freezing method, conserved the function of the shoulder joint. To our knowledge, this is the first case of a disseminated PMT in the bone that was treated with a frozen autograft, and this treatment method may be effective for cases in which curettage for PMT in the bone would be inevitably inadequate.